PERAN KERJA KERAS DAN KERJA CERDAS MELALUI MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN AGENT ASURANSI (Studi Pada PT. Prudential Life Assurance Surabaya) - Rudi Hartono; Mochammad Isa Anshori (Kompetensi (Competence : Journal of Management Studies), 2019)
This study aims to empirically examine the role of hard work and smart work through work motivation in improving the performance of insurance agents PT. Prudential Life Assurance Surabaya, this analysis uses an independent variable that is the variable of hard work, smart work and work motivation. For the dependent variable is the performance of the sample of this study is the insurance agent PT. Prudential Life Assurance Surabaya Titans Surabaya office unit. The sample is done by random sampling method. Collecting data by distributing questionnaires directly to insurance agents as many as 91 respondents. The statistical method uses multiple linear analysis, by testing the hypothesis R test, t test and f test. the results of this study indicate that hard work, smart work and work motivation have a positive and significant effect on the performance of insurance agents, and the most dominant influence is an indirect relationship with the performance of insurance agents.